Erratum to: The UBC-40 Urothelial Bladder Cancer Cell Line Index: a genomic resource for functional studies. (December 2015) - Earl, Julie; Rico, Daniel; Carrillo-de-Santa-Pau, Enrique; Rodríguez-Santiago, Benjamín; Méndez-Pertuz, Marinela; Auer, Herbert; Gómez, Gonzalo; Grossman, H.; Pisano, David; Schulz, Wolfgang; Pérez-Jurado, Luis; Carrato, Alfredo; et al.
ᅟ ᅟ ᅟ